PENGARUH GAYA HIDUP DAN KEMUDAHAN TERHADAP MINAT BELI MAHASISWA DALAM BERBELANJA ONLINE - Rumbiati Rumbiati; Heriyana Heriyana (Politeknik Negeri Sriwijaya, 2020)
The development of technology makes the internet a medium that is not only used as a medium of communication, but also a shopping medium. The purpose of this paper is to see how the effect of lifestyle and ease of use on college student interest in shopping online. This research is a descriptive and parametric study. The data used are primary data, processing using data with ANOVA (analysis of variance) test. The sampling technique used was purposive sampling with a total sample of 205. The results showed that lifestyle and ease of use affect the buying interest of college students in shopping online. From the economic side, online shopping can reduce the activity/ sacrifice that is considered as expenditure.